Costs associated with nonalcoholic steatohepatitis disease progression in Medicare patients: a retrospective cohort study - Yestle Kim; Joseph Medicis; Matthew Davis; Dominic Nunag; Robert Gish (Becaris Publishing Limited, 2024)
Aim: Non-alcoholic steatohepatitis (NASH), ormetabolic dysfunction-associated steatohepatitis (MASH), is a severe form of non-alcoholic fatty liver disease (NAFLD) ormetabolic dysfunction-associated liver disease (MASLD), that may progress to advanced liver disease. Costs associated with progression are not well characterized. This study sought to quantify costs and healthcare resource utilization (HRU) associated with NASH progression. Methods: Patients were included if diagnosed with NASH (ICD-10: K75.81) in 100% Medicare claims data (2015-2021) who were ≥66 years at index (diagnosis), continuously enrolled in Parts A, B and D for ≥12 months prior to and 6 months following index (unless death) and who had no evidence of other causes of liver disease. Patient-time was categorized into five severity states: non-cirrhotic NASH, compensated cirrhosis (CC), decompensated cirrhosis (DCC), hepatocellular carcinoma (HCC) and liver transplant (LT). Annualized HRU and costs were calculated during the study periods overall and stratified by occurrence and timing of progression. Results: In 14,806 unique patients (n = 12,990 noncirrhotic NASH; 1899 CC; 997 DCC; 209 HCC; 140 LT), mean age and follow-up were 72.2 and 2.8 years, respectively. Average annualized costs increased from baseline following diagnosis, generally scaling with severity: $16,231 to $27,044; $25,122 to $57,705; $40,613 to $181,036; $36,549 to $165,121 and $35,626 to $108,918 in NASH; CC; DCC; HCC; and LT; respectively. Non-cirrhotic NASH and CC patients with progression had higher follow-up spending (1.6x for NASH; 1.7x for CC) than non-progressors (both p < 0.001), 2.8 and 6.1-times higher odds of an inpatient stay and 2.6 and 3.6-times higher odds to be in the top 20% of spenders, respectively, relative to non-progressors (both p < 0.001). Patients progressing within a year had costs 1.4, 1.6, 1.7 and 2.2-times more than year 2, 3, 4 and 5 progressors' costs, respectively, for noncirrhotic NASH and 1.3, 1.8, 2.0 and 2.2-times more than year 2, 3, 4 and 5 progressors' costs, respectively, for CC. Conclusion: NASH progression is associated with high costs that increase in more severe disease states. Slower progression is associated with lower costs, suggesting a potential benefit of therapies that may delay or prevent progression.